The Implementation of Reflective Teaching Strategies in Secondary School in Surabaya - Safi’i, Nissak Azizah Ayu (RETAIN : Journal of Research in English Language Teaching, 2025)
Reflective teaching is a successful instructional technique in which teachers evaluate their performance, evaluate others, evaluate their methods, and welcome honest feedback from those who are willing to learn. Mathew’s Reflective Teaching Strategies theory, explains that seven aspects can be used in implementing reflective teaching strategies, namely, Reflective Journals/Diaries, Collaborative Learning, Recording Lessons, Educator Feedback, Peer Observation, Student Feedback, and Action Research. The purpose of this study is to find out how teachers implement reflective teaching strategies in the classroom and how consistently or how often teachers implement them. The researcher used descriptive qualitative and the data analysis was conducted in two stages. The first stage is observation. Observations were conducted in two classes in one private school in West Surabaya and the interview was conducted with one English teacher. The results showed that the teacher used four of the seven characteristics of reflective teaching. Based on the findings from this study, it can be said that the teacher applied reflective teaching methods during the learning process. As a result, the teacher consistently uses reflective teaching practices and strives to innovate their teaching in every meeting.